2020
DOI: 10.3390/ijerph17165674
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Muscular Strength on Depression Symptoms in Adults: A Systematic Review and Meta-Analysis

Abstract: The aim was to systematically review the relationship between muscular strength (MS) and depression symptoms (DS) among adults, and conduct a meta-analysis to determine the pooled odds ratio (OR) for the relationship between MS and DS. The strategies employed in this systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Studies published up to December 2019 were systematically identified by searching in the PubMed, Scopus, and Web of Science elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 55 publications
8
39
0
4
Order By: Relevance
“…Muscular fitness was measured through two strength tests to best evaluate for muscular strength and endurance, given the variability of muscular fitness across sexes. Muscular fitness and its inverse association with depressive symptoms have been previously investigated (Marques et al, 2020). This association was also shown in this study after multivariable analysis, showing that participants in the highest subset of muscular fitness demonstrated a BDI-II score lower than participants with low fitness scores.…”
Section: Discussionsupporting
confidence: 82%
“…Muscular fitness was measured through two strength tests to best evaluate for muscular strength and endurance, given the variability of muscular fitness across sexes. Muscular fitness and its inverse association with depressive symptoms have been previously investigated (Marques et al, 2020). This association was also shown in this study after multivariable analysis, showing that participants in the highest subset of muscular fitness demonstrated a BDI-II score lower than participants with low fitness scores.…”
Section: Discussionsupporting
confidence: 82%
“…A recent systematic review of 21 studies on the effect of muscular strength on depressive symptoms 5 included data from 11 cross‐sectional studies that reported associations between depressive symptoms and low HGS 16–26 and one that detected no association 27 . Two of the included studies found that the associations were evident in women but not men, 21,23 confirming previously observed sex dimorphism 28 and found in our study.…”
Section: Discussionsupporting
confidence: 88%
“…There have also been efforts to identify and optimize diagnostic cutpoints according to their ability to discriminate poor physical function. Extant literature demonstrates an association between poor physical and mental health 5,6 . It is thus feasible that psychological well‐being could affect physical performance, yet there has been no consideration of how symptoms of depression and anxiety might influence the selection of criteria and cutpoints for identifying sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the association between handgrip strength and depression is complicated and has been described in previous studies. 7 , 13 First, low handgrip strength is an indicator of sarcopenia, which is strongly related to adverse outcomes, such as major complications, extended hospital stays, and lower quality 38 of life, thus increasing the likelihood of depression when patients experience these adverse clinical outcomes. A meta-analysis reported that sarcopenia increases the risk of depression (pooled OR=1.821, 95% CI: 1.16–2.85).…”
Section: Discussionmentioning
confidence: 99%
“… 17–19 Meanwhile, a recent meta-analysis showed that muscle strength has a positive impact on reducing depression, with a pooled OR of 0.85 (95% CI: 0.80–0.89). 7 …”
Section: Introductionmentioning
confidence: 99%